Analisis Penyajian Laporan Keuangan Sebelum dan Sesudah Penerapan SAK Syariah: Studi Kasus pada KSPPS BMT NU Jombang - Aulia Azzahro Putri; Dwi Ermayanti Susilo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the presentation of financial statements before and after the implementation of Sharia Financial Accounting Standards (SAK Syariah) at KSPPS BMT NU Jombang. The research employs a qualitative approach using a case study method, with data collected through interviews, observations, and financial document analysis. The analysis focuses on differences in the completeness of financial statement components, conformity of reporting formats, account classification, and the extent of disclosure before and after the implementation of SAK Syariah. The findings indicate that prior to the adoption of SAK Syariah, financial statements were presented in a simplified manner. After the implementation, financial statements were prepared more comprehensively and systematically in accordance with Sharia Accounting Standards, including cash flow statements, statements of changes in equity, and notes to the financial statements. The application of SAK Syariah enhances transparency, comparability, and decision usefulness of financial information. Therefore, this study highlights the crucial role of SAK Syariah in improving the quality of financial statement presentation in sharia cooperatives.